2009
DOI: 10.1111/j.1477-2574.2009.00006.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of remote ischemic preconditioning on hepatic microcirculation and function in a rat model of hepatic ischemia reperfusion injury

Abstract: Using intravital microscopy, this study demonstrates that RIPC modulates hepatic microcirculation to reduce the effects of IRI. HO-1 may have a key role in the modulation of hepatic microcirculation and endothelial function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 42 publications
3
45
0
Order By: Relevance
“…Several publications concerning the use of RIPC were published after the initial study of Kanoria 7 and the results were encouraging, as liver protection form IRI was uniformly identified [7][8][9][10]15 . Similar to these results, the present study demonstrates RIPC is effective in decreasing liver necrosis, as it shows a significant reduction of tissue necrosis in the RIPC group when compared to the I/R group (Figures 1 and 2).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Several publications concerning the use of RIPC were published after the initial study of Kanoria 7 and the results were encouraging, as liver protection form IRI was uniformly identified [7][8][9][10]15 . Similar to these results, the present study demonstrates RIPC is effective in decreasing liver necrosis, as it shows a significant reduction of tissue necrosis in the RIPC group when compared to the I/R group (Figures 1 and 2).…”
Section: Discussionmentioning
confidence: 98%
“…More recently, several investigators studied the use of RIPC to reduce liver I/R injury [7][8][9][10] . All studies showed a protective effect in liver IRI, but the underlying mechanisms involved in RIPC have not yet been established 11 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, IR injury has become a topic of particular interest in the context of liver surgery and research. Studies have predominantly focused on RIPC, which is a strategy for harnessing the body's endogenous protective capabilities against the injury that is incurred during IR (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). NO is an essential mediator of the protection that is afforded by hind-limb RIPC against liver IR injury (25).…”
Section: Discussionmentioning
confidence: 99%
“…The protective mechanism of RIPC is highly complex (18)(19)(20)(21)(22) and involves the improvement of hepatic oxygenation (23), reduction of serum cytokine-induced neutrophil chemoattractant-1 levels (24), modulation of hepatic microcirculation (15) and activation of the soluble guanylate cyclase-cyclic guanosine monophosphate pathway (20), resulting in protective effects against IR injury. Notably, Abu-Amara et al (25) suggested that nitric oxide (NO) is an essential mediator of the protection that is afforded by hind-limb RIPC against liver IR injury.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation